Abnormal Haemodynamic Flow Patterns in Bicuspid Pulmonary Valve Disease - Bissell, Malenka M.; Loudon, Margaret; Neubauer, Stefan; Myerson, Saul G. (Frontiers in Physiology, 2017)
Abnormal flow patterns in the aortas of those with bicuspid aortic valves are increasingly recognized as important in the pathogenesis of aortic dilatation but pulmonary flow patterns in bicuspid pulmonary valves have not been studied. Bicuspid pulmonary valve disease is rare and a small numbers of case reports describe concomitant pulmonary artery dilation similar to the dilation of the ascending aorta, which is often seen in bicuspid aortic valve disease. We examined three cases of bicuspid pulmonary valve disease, 10 healthy volunteers and 10 patients with bicuspid aortic valve disease but a tricuspid pulmonary valve. All participants underwent anatomical and functional imaging of the pulmonary valve, pulmonary artery and right ventricle as well as advanced time-resolved 3-dimensional cardiac magnetic resonance imaging (4D flow) to assess the flow pattern in the pulmonary artery. All patients with a bicuspid pulmonary valve had pulmonary artery dilation and showed distinct helical flow abnormalities with increased rotational flow and increased flow displacement compared to a mild left-handed flow pattern in the healthy volunteers. Additionally, there was marked asymmetry seen in the systolic wall shear stress pattern, with the highest values in the anterior wall of the pulmonary artery. In comparison, patients with a bicuspid aortic valve but a tricuspid pulmonary valve had normal flow patterns in the pulmonary artery. These haemodynamic findings are similar to recent studies in bicuspid aortic disease, and suggest the importance of flow patterns in the pathophysiology of vessel dilation in both aortic and pulmonary bicuspid valve disease.